GHRL Gene Leu72Met Polymorphism and Type 2 Diabetes Mellitus: A Meta-Analysis Involving 8,194 Participants - Li, Yan-yan; Lu, Xin-zheng; Yang, Xin-xing; Wang, Hui; Geng, Hong-yu; Gong, Ge; Zhan, Yi-yang; Kim, Hyun Jun; Yang, Zhi-jian (Frontiers in Endocrinology, 2019)
Background: Although many studies indicate a positive correlation between GHRL gene Leu72Met polymorphism and an increased susceptibility to type 2 diabetes mellitus (T2DM), inconsistencies between independent studies still remain. Objective: Considering the inconsistencies between them, we have performed the current meta-analysis study. The objective of this study is to better examine the correlation of the GHRL gene Leu72Met polymorphism and T2DM. Methods: The current meta-analysis, involving 8,194 participants from 11 independent studies, was performed. A fixed effect model was used to evaluate the pooled odds ratios (ORs) and the corresponding 95% confidence intervals (95% CIs). Results: A significant association was found between T2DM and GHRL gene Leu72Met polymorphism under recessive (OR: 1.33, 95% CI: 1.01–1.76, P=0.04), and homozygous genetic models (OR: 1.34, 95% CI: 1.01–1.78, P=0.04) in the whole population. The correlation was more distinct in our subgroup analysis of the Chinese population under recessive (OR: 1.52, 95% CI: 1.07–2.15, P=0.02), dominant (OR: 1.70, 95% CI: 1.38-2.10, P<0.00001), additive (OR: 1.16, 95% CI: 1.02–1.33, P = 0.02), and homozygous genetic models (OR: 1.54, 95% CI: 1.07–2.20, P=0.02). Conclusions: In short, GHRL gene Leu72Met polymorphism was significantly correlated with increased T2DM risk, particularly in the Chinese population. Individuals carrying the Met72 allele of GHRL Leu72Met gene polymorphism, particularly those of Chinese ancestry, may be more susceptible to developing T2DM disease.